Morphology of ammonium perchlorate in the presence of ethylene glycol as an additive: a first principle study - Khan, Md Abdul Shafeeuulla; Vijayalakshmi, R.; Singh, Avtar; Nandi, Amiya Kumar; Talawar, M. B. (Crystengcomm, 2019)
Ammonium perchlorate (AP) is an extensively used crystalline oxidizer in high energy materials and their compositions. A desired morphology of AP is crucial for the high burn rates of solid propellants. We have examined the habit modification of AP crystals in the absence and presence of ethylene glycol as an impurity by means of important parameters such as interaction and surface energies to predict the resultant morphology. On the basis of first principles density functional theory (DFT) calculations of the binding and surface energies before and after the adsorption of the surface-capping agent (ethylene glycol) on the AP surfaces, we have shown that the relative stability of all the important surfaces (100), (101), (011), (001) and (210) rationalize the habit modification of AP crystals. In accordance with the surface energy calculations, the stability order of the five crystallographic surfaces of AP was found to be (001) > (210) > (101) > (100) > (011) in the absence of additive molecules, i.e., in the clean surfaces. This result is in concurrence with the fact that AP crystals richly contain (001) planes when grown in the absence of an additive. The computational methodology applied for the determination of surface energies was found to be reliable as it has well reproduced the stability trend of AP surfaces. However, the trend, (210) > (001) > (101) > (011) > (100), was observed when these surfaces were capped with a known additive molecule, i.e., ethylene glycol. The crystal habit of AP in the presence of ethylene glycol is such that the intensity of the lattice plane (2 1 0) of the modified AP was remarkably high leading to the shape of hexahedral, which is in excellent agreement with the experimental results. A linear fit correlation was also observed between surface energies and interaction energy values for the additive adsorbed AP surfaces.